Cytosolic phospholipase A(2)α and eicosanoids regulate expression of genes in macrophages involved in host defense and inflammation. - Saritha Suram; Lori J Silveira; Spencer Mahaffey; Gordon D Brown; Joseph V Bonventre; David L Williams; Neil A R Gow; Donna L Bratton; Robert C Murphy; Christina C Leslie (PLoS ONE)
The role of Group IVA cytosolic phospholipase A2 (cPLA2α) activation in regulating macrophage transcriptional responses to Candida albicans infection was investigated. cPLA2α releases arachidonic acid for the production of eicosanoids. In mouse resident peritoneal macrophages, prostacyclin, prostaglandin E2 and leukotriene C4 were produced within minutes of C. albicans addition before cyclooxygenase 2 expression. The production of TNFα was lower in C. albicans-stimulated cPLA2α(+/+) than cPLA2α(-/-) macrophages due to an autocrine effect of prostaglandins that increased cAMP to a greater extent in cPLA2α(+/+) than cPLA2α(-/-) macrophages. For global insight, differential gene expression in C. albicans-stimulated cPLA2α(+/+) and cPLA2α(-/-) macrophages (3 h) was compared by microarray. cPLA2α(+/+) macrophages expressed 86 genes at lower levels and 181 genes at higher levels than cPLA2α(-/-) macrophages (≥2-fold, p<0.05). Several pro-inflammatory genes were expressed at lower levels (Tnfα, Cx3cl1, Cd40, Ccl5, Csf1, Edn1, CxCr7, Irf1, Irf4, Akna, Ifnγ, several IFNγ-inducible GTPases). Genes that dampen inflammation (Socs3, Il10, Crem, Stat3, Thbd, Thbs1, Abca1) and genes involved in host defense (Gja1, Csf3, Trem1, Hdc) were expressed at higher levels in cPLA2α(+/+) macrophages. Representative genes expressed lower in cPLA2α(+/+) macrophages (Tnfα, Csf1) were increased by treatment with a prostacyclin receptor antagonist and protein kinase A inhibitor, whereas genes expressed at higher levels (Crem, Nr4a2, Il10, Csf3) were suppressed. The results suggest that C. albicans stimulates an autocrine loop in macrophages involving cPLA2α, cyclooxygenase 1-derived prostaglandins and increased cAMP that globally effects expression of genes involved in host defense and inflammation.